Shadows of the White City [large type] - Green, Jocelyn (Green, Jocelyn. Windy City saga, 2021)
"She promised a dying father she would keep his daughter safe. She can't fail now. The one thing Sylvie Townsend wants most is what she feared she would never have - a family of her own. But taking in Polish immigrant Rose Dabrowski to raise and love quells those fears - until seventeen-year-old Rose goes missing at the World's Fair, and Sylvie's life unravels. With nowhere else to turn, Sylvie seeks help from her boarder and Rose's violin instructor, Kristof Bartok. Fluent in several languages, his skills are vital to helping Sylvie navigate the immigrant and international communities where their investigation leads. From the glittering architecture of the Fair to the dark houses of Chicago's poorest neighborhoods, they're taken on a search that points to Rose's long-lost family. Is Sylvie willing to let the girl go? And as Kristof and Sylvie grow closer, can she reconcile her craving for control with her yearning to belong?"--